Self Actualization of MOSMA Participants in Maintaining Cultural Identity in Scotland, United Kingdom - Rusnali, Andi Nur Aisyah; Halimah, Mujammilatul (Palakka : Media and Islamic Communication, 2024)
The importance of preserving and maintaining cultural identity has become a major highlight amidst ever-growing globalizations. In the context of student exchange, an interesting initiative has emerged in the Mora Overseas Student Mobility Award (MOSMA) program. This research aims to abstract the contributions and experiences of MOSMA participants in efforts to maintain Indonesian cultural identity in Scotland, United Kingdom. This research uses qualitative research methods with participant observation. Data collection was carried out by conducting in-depth interviews with MOSMA participants from various backgrounds. The research results show that MOSMA is not only a program for learning in the academic field but also a place to gain in-depth cultural experiences. MOSMA participants are actively involved in various activities, such as regular international student meetings, cultural discussions, introductions to traditional music and songs, all of which play an important role in maintaining and introducing Indonesia's cultural identity abroad. Apart from that, MOSMA also provides a platform to develop social skills, independence and a sense of belonging to the nation's cultural heritage. Through MOSMA, participants can feel a sense of pride in Indonesia's cultural identity, thereby strengthening their commitment to passing it on to future generations. In conclusion, MOSMA has proven itself as an effective program initiative in maintaining and strengthening Indonesia's cultural identity amidst globalizations. By continuing to provide adequate support and attention, MOSMA has the potential to become an inspiring model in maintaining cultural diversity throughout the world.